Wabah Menular dalam Karya Sastra - Eva Farhah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
Infectious plague has seized the attention of a number of experts in various scientific fields and squeezed a number of dimensions of human life. This is also inseparable from the attention of Arabic writers, Egypt, namely Thaha Husain in undergoing an infectious plague era. Through his work entitled Al-Mu'tazilah (1971), Thaha Husain highlights the individual and social conditions of the community at the time when an outbreak of an infectious virus struck and after it passed. This situation is the problem in this study. Thus, the purpose of this study is to describe, describe and critique the attitudes of individuals and social communities in the face of infectious plague. The various attitudes and behaviors presented in this literary text serve as primary research data and are analyzed by descriptive methods. That is an analytical method that emphasizes the description of a qualitative critical analysis data, and not produce numbers as quantitative research. Furthermore, literary reception theory is used to express research analysis by its work, namely the method of textual criticism in order to obtain an objective and scientific analysis, then reinforced by secondary sources related to research. Thus, the results of this study are exemplary individual and social attitudes that can be implemented in contemporary life in the context of prevention, treatment and mutual assistance in dealing with infectious virus outbreaks. In addition, people can refrain from doing things that can harm the social environment.